2009
DOI: 10.1038/emboj.2009.147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of histone lysine methylation by the Polycomb group repressor dSfmbt

Abstract: Polycomb group (PcG) proteins repress transcription by modifying chromatin structure in target genes. dSfmbt is a subunit of the Drosophila melanogaster PcG protein complex PhoRC and contains four malignant brain tumour (MBT) repeats involved in the recognition of various mono-and dimethylated histone peptides. Here, we present the crystal structure of the four-MBT-repeat domain of dSfmbt in complex with a mono-methylated histone H4 peptide. Only a single histone peptide binds to the four-MBT-repeat domain. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 34 publications
1
117
0
1
Order By: Relevance
“…In contrast, Context Mirror predicts the PHO/SFMBT interaction (Alfieri et al, 2013) and the well-characterized interactions between these two subunits of the PhoRC complex and those of PRC1: PHO/PC (Mohd-Sarip et al, 2002), PHO/PH-P (Mohd- Sarip et al, 2002) and SFMBT/SCM (Grimm et al, 2009). The bioinformatic method also predicts the well-established interactions between subunits of the PRC1 complex, that is, PH-P/PC (Strutt and Paro, 1997), PH-P/PSC (Kyba and Brock, 1998), PH-P/SCM (Peterson et al, 1997), PC/PSC (Kyba and Brock, 1998), PC/SCE and PSC/SCE (Gorfinkel et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, Context Mirror predicts the PHO/SFMBT interaction (Alfieri et al, 2013) and the well-characterized interactions between these two subunits of the PhoRC complex and those of PRC1: PHO/PC (Mohd-Sarip et al, 2002), PHO/PH-P (Mohd- Sarip et al, 2002) and SFMBT/SCM (Grimm et al, 2009). The bioinformatic method also predicts the well-established interactions between subunits of the PRC1 complex, that is, PH-P/PC (Strutt and Paro, 1997), PH-P/PSC (Kyba and Brock, 1998), PH-P/SCM (Peterson et al, 1997), PC/PSC (Kyba and Brock, 1998), PC/SCE and PSC/SCE (Gorfinkel et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…This small-scale differentiation facilitates effective identification of candidate genes influenced by spatially varying selection. Figure 4 shows one example in which a 1-kb windows in the top 2.5% F ST tail localizes to Sfmbt, a chromatin-binding protein involved in gene regulation (Grimm et al 2009). A genome browser displaying 1-kb windows and their associated F ST estimates is available at http:/ / altair.dartmouth.edu/ucsc/index.html.…”
Section: à16mentioning
confidence: 99%
“…41 In vitro studies using isolated MBT domains and histone peptides have demonstrated a general preference for binding to mono-or di-methylated, over un-or tri-methylated peptides. 27,[42][43][44][45][46][47][48][49] An exception to this general rule is provided by the Caenorhabditis elegans protein LIN-61, which displays specificity toward di-and tri-methylated H3K9 histone peptides. 50 A recent study investigating the MBT domains of all 9 human family members has found that some MBT domains (L3MBTL1, L3MBTL3) recognize mono-and/or di-methyl-lysine in a promiscuous, non-sequence-specific fashion, whereas others (SCML2, L3MBTL4, MBTD1, L3MBTL2) specifically bind to only a few selected histone sequences.…”
Section: -23mentioning
confidence: 99%